2014
DOI: 10.18388/abp.2014_1884
|View full text |Cite
|
Sign up to set email alerts
|

Expression of avian influenza haemagglutinin (H5) and chicken interleukin 2 (chIL-2) under control of the ptcB promoter in Lactococcus lactis.

Abstract: Gram-positive and nonpathogenic lactic acid bacteria (LAB) are considered to be promising candidates for the development of new, safe systems of heterologous protein expression. Recombinant LAB has been shown to induce specific local and systemic immune response against selected pathogens, and could be a good alternative to classical attenuated carriers. The main goal of our study was to express the avian influenza haemagglutinin (H5) and chicken interleukin 2 (chIL-2) in Lactococcus lactis. Results of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A positive effect (induction of the specific antibodies and reduction of the level of colonization of mice by H. felis ) was only seen after vaccination with a Lactobacillus strain (Lee et al 2001 ; Corthesy et al 2005 ). It is postulated that some L. lactis strains that reveal high affinity to mucus are promising candidates for development of a vaccine against bird flu (Szatraj et al 2014 ; Radziwill-Bienkowska et al 2014 ).…”
Section: Lab As Carriers Of Heterologous Bacterial Parasitic and VImentioning
confidence: 99%
See 1 more Smart Citation
“…A positive effect (induction of the specific antibodies and reduction of the level of colonization of mice by H. felis ) was only seen after vaccination with a Lactobacillus strain (Lee et al 2001 ; Corthesy et al 2005 ). It is postulated that some L. lactis strains that reveal high affinity to mucus are promising candidates for development of a vaccine against bird flu (Szatraj et al 2014 ; Radziwill-Bienkowska et al 2014 ).…”
Section: Lab As Carriers Of Heterologous Bacterial Parasitic and VImentioning
confidence: 99%
“…Coproduction induced significantly higher levels of specific IgG antibodies than when L. lactis produced only TTFC (Steidler et al 1995 , 1998a ). The use of L. lactis expressing chicken interleukin 2 (chIL-2) together with avian influenza hemagglutinin (H5) also revealed adjuvant properties of chIL-2, and the study suggests that L. lactis could be a promising candidate as antigen carrier in vaccines against avian flu (Szatraj et al 2014 ). In recent years, the influence of IL-12 on the immune system has been extensively studied.…”
Section: Modulation Of the Activity Of The Immune Systemmentioning
confidence: 99%
“…The mucosal delivery systems include live bacterial vectors and among them those that use commensal bacteria, such as lactobacilli or certain streptococci and staphylococci. We have shown that using Lactococcus as a producer of an influenza virus antigenic protein, haemagglutinin, is a promising approach (Szatraj et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have shown that it is possible to engineer L. lactis cells to produce the H5 protein of the avian influenza virus H5N1 [33]. In this study, we aimed at further improvement of the approach.…”
Section: Discussionmentioning
confidence: 99%